An In-Depth Semantic Analysis of Denotative and Connotative Meaning in the Song Lyrics of ‘Let Her Go’ by Passenger - Yenni Adelina Sinaga; Bernieke Anggita Ristia Damanik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the semantic construction of denotative and connotative meanings in the song lyrics of “Let Her Go” by Passenger through a non-empirical qualitative design grounded in Geoffrey Leech’s theory of meaning. The analysis focuses on how literal lexical references and implied emotional significations interact to produce layered interpretations within lyrical discourse. Data were obtained from the complete song lyrics and analyzed through close reading, semantic categorization, and contextual interpretation. The findings reveal that denotative meanings function as structural anchors that provide literal clarity, while connotative meanings dominate the interpretive dimension by expressing emotional experiences such as regret, loneliness, love, and realization. The study further identifies that repetition, symbolism, metaphor, and binary oppositions such as light and darkness significantly contribute to semantic depth and thematic coherence. Interaction between denotative and connotative layers forms a unified interpretive system that enables emotional resonance and narrative progression. The research concludes that semantic analysis is essential in revealing the complex relationship between literal and emotional meanings in song lyrics.